2019
DOI: 10.17559/tv-20181102185923
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Influence of Product Development on Business Performance and Competitiveness in Manufacturing Enterprises

Abstract: In this paper the influence of product innovation and development on business performance and competitiveness in small and medium-sized manufacturing enterprises is addressed. The research was conducted via survey and it included over 2200 manufacturing enterprises from Serbia. The number of returned and usable surveys was 132 (5.98% return rate). The regression model included product development and innovation as two important engineering endeavours and business performance and competitiveness. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(31 reference statements)
1
3
0
1
Order By: Relevance
“…The research results presented in this paper confirmed, similarly to previous research, the impact of quality on business performance (Portela & Thanassoulis, 2005;Fening, 2012;Saleem & Raja, 2014;Cvjetković et al, 2017;Bakator et al, 2019) and the customer satisfaction (Osman & Sentosa, 2003;Bostos & Gallega, 2008;Chai et al, 2009;Saleem & Raja, 2014;Blut et al, 2015). The contribution of this research is reflected in the fact that the principles of quality management had been identified, which achieved the greatest impact on improving business performance and customer satisfaction.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The research results presented in this paper confirmed, similarly to previous research, the impact of quality on business performance (Portela & Thanassoulis, 2005;Fening, 2012;Saleem & Raja, 2014;Cvjetković et al, 2017;Bakator et al, 2019) and the customer satisfaction (Osman & Sentosa, 2003;Bostos & Gallega, 2008;Chai et al, 2009;Saleem & Raja, 2014;Blut et al, 2015). The contribution of this research is reflected in the fact that the principles of quality management had been identified, which achieved the greatest impact on improving business performance and customer satisfaction.…”
Section: Discussionsupporting
confidence: 90%
“…The research (Bakator et al, 2019) indicates that product development and innovation have a statistically significant impact on business performance and competitiveness. Quality ensures organizations gain competitive advantage and contributes to their growth and business performance (Fening, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The only way for enterprises to become competitive is to eliminate the lock at the low end of the value chain, create high added value, and gradually climb to both ends of the value chain. Service transformation and product innovation provide two paths for enterprises to gain competitiveness (Vargo & Lusch, 2004;Bakator et al, 2019). Service transformation essentially belongs to business model innovation Visnjic et al, 2016).…”
Section: Theoretical Mechanism and Research Hypothesismentioning
confidence: 99%
“…On the other hand, market demand and consumption preference change with the passing of time, and innovation only for existing products may not fully match changing market trends. Therefore, manufacturing enterprises can also capture future development trends based on new market demands to develop new products and provide diversified and differentiated products in the market to achieve excess profits while also expanding the market sales range, ultimately enhancing enterprise competitiveness (Rauf et al, 2023;Bakator et al, 2019).…”
Section: Theoretical Mechanism and Research Hypothesismentioning
confidence: 99%
“…Finalmente, un problema importante del sector manufacturero colombiano es la falta de compromiso por parte de las empresas, respecto a los requerimientos de un mercado competitivo, es decir, la ausencia de políticas estructurales encaminadas a potenciar la industria para la competitividad internacional (López Riveros, 2013). Por este motivo es fundamental que los ejecutivos de las empresas sean conscientes de la relevancia de los procesos de innovación en las empresas (BID, 2016), pues sin esta no podrían ser competitivas en este mundo globalizado y globalizante (Bakator, et al, 2019). De acuerdo con los miembros de la ANDI, los principales agravantes en este punto -a saber, los factores que en mayor medida obstaculizan la dinámica del sector-son: el decrecimiento de la producción económica y el aumento del contrabando, debido al ingreso de productos ilegales al país como resultado de las aperturas comerciales; y la poca inversión extranjera, a causa de los problemas de seguridad y conflicto que ha tenido que afrontar el país por varios años (Chasqui Uribe y Soto Valderrama, 2016).…”
Section: Contextualización De La Problemáticaunclassified